2020
DOI: 10.31665/jfb.2020.9216
|View full text |Cite
|
Sign up to set email alerts
|

Brazil nut: nutritional benefits from a unique combination of antioxidants

Abstract: Brazil nut is the seed of the Bertholletia excelsa tree, which grows naturally in the rainforests of South America. The production chain is environmentally sustainable as seeds are collected from the hard-shelled indehiscent fruits as they fall on the forest floor, without the need of deforestation. Brazil nut is among the most popular and commercially important tree nuts, and a reduced risk of coronary heart disease among other health benefits have been related to their consumption. A high content of both sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Leandro et al [40] showed that Brazil nut waste can be used as flour to produce fibers, oligosaccharides, fertilizers, and energy. Sartori et al [41] showed that a combination of antioxidant compounds, such as flavonoids, tocopherols, selenium, oleic acid, and linoleic acid, and other compounds that have anti-inflammatory activities in humans are present in the nuts and their residues.…”
Section: Cereals Nuts and Seedsmentioning
confidence: 99%
“…Leandro et al [40] showed that Brazil nut waste can be used as flour to produce fibers, oligosaccharides, fertilizers, and energy. Sartori et al [41] showed that a combination of antioxidant compounds, such as flavonoids, tocopherols, selenium, oleic acid, and linoleic acid, and other compounds that have anti-inflammatory activities in humans are present in the nuts and their residues.…”
Section: Cereals Nuts and Seedsmentioning
confidence: 99%
“…Therefore, the high concentration of ellagic acid in jua pulp extracts may render a significant contribution to its bioactive properties, classifying jua as an alternate source for the recovery of ellagic acid. Other sources of ellagic acid include pecans [22], Brazil nuts [23], fennel seed [24], mango seed, longan seed, pomegranate peel, walnuts' skin, and other underutilized fruits such as Canarium odontophyllum, Dacryodes rostrata, Mangifera pajang, and Parkia speciosa [25][26][27][28].…”
Section: Identification Of Phenolic Compounds By High-performance Liquid Chromatography (Hplc)mentioning
confidence: 99%